Digestibilidade aparente do triticale para a tilápia-do-nilo - Tachibana, Leonardo (2010)
This work aimed to determine the dry matter (DM), crude protein (CP), gross energy (GE) and essential aminoacid (EAA) digestibility coefficient of triticale by Nile tilapia. Fish with 112.00 ± 22.00g average weight were used to digestibility test. Reference diet was formulated with purified ingredients and triticale replaced 30% of this diet. Chromic oxide was used as an external inert marker to determine the digestibility coefficients. The apparent digestibility coefficients (ADC) of triticale were (%): 70.98; 87.33 ± 1.64; 72.87 ± 0.35; DM, CP and GE, respectively; alanine 80.45; arginine 94.88; aspartic acid 84.59; glycine 83.82; isoleucine 84.08; leucine 89.43; lysine 83.70; cysteine 99.87; methionine 76.38; phenylalanine 91.04; tyrosine 78.61; threonine 76.83; tryptophan 87.10; proline 97.64; valine 88.05; histidine 93.52; serine 87.76. Results demonstrated good quality of triticale nutrients to Nile tilapia feeds.